Noninvasive mechanical ventilation in the COVID‐19 era: Proposal for a continuous positive airway pressure closed‐loop circuit minimizing air contamination, oxygen consumption, and noise. Issue 7 (26th January 2021) - Cavaglià, Marco; Olivieri, Carlo; Morbiducci, Umberto; Raparelli, Terenziano; Jacazio, Giovanni; Ivanov, Alexandre; Chiesa, Alessandro; Savino, Dario; Chiarenza, Sebastiano M.; Romiti, Armando; Romiti, Andrea; Ferrara, Marino; et al.
Abstract: Noninvasive continuous positive airway pressure (NIV‐CPAP) is effective in patients with hypoxemic respiratory failure. Building evidence during the COVID‐19 emergency reported that around 50% of patients in Italy treated with NIV‐CPAP avoided the need for invasive mechanical ventilation. Standard NIV‐CPAP systems operate at high gas flow rates responsible for noise generation and inadequate humidification. Furthermore, open‐configuration systems require a high concentration of oxygen to deliver the desired FiO2 . Concerns outlined the risk for aerosolization in the ambient air and the possible pressure drop in hospital supply pipes. A new NIV‐CPAP system is proposed that includes automatic control of patient respiratory parameters. The system operates as a closed‐loop breathing circuit that can be assembled, combining a sleep apnea machine with existing commercially available components. Analytical simulation of a breathing patient and simulation with a healthy volunteer at different FiO2 were performed. Inspired and expired oxygen fraction and inspired and expired carbon dioxide pressure were recorded at different CPAP levels with different oxygen delivery. Among the main findings, we report (a) a significant (up to 30‐fold) reduction in oxygen feeding compared to standard open high flow NIV‐CPAP systems, to assure the same FiO2 levels, and (b) a negligible production of the noise generated in ventilatory systems, and consequent minimization of patients' discomfort. The proposed NIV‐CPAP circuit, reshaped in closed‐loop configuration with the blower outside of the circuit, has the advantages of minimizing aerosol generation, environmental contamination, oxygen consumption, and noise to the patient. The system is easily adaptable and can be implemented using standard CPAP components. Abstract : A CPAP machine for sleep apnea was used as a flow generator to test a closed‐loop breathing circuit pressurizing the helmet chosen as patient's interface. The circuit was assembled using standard anesthesia equipment and was carefully monitored by an anesthesia gas analyzer. This configuration brings new benefits to non‐invasive CPAP ventilation in terms of low oxygen requirement, insignificant leak pollution, and negligible levels of noise within the interface.